TEKNIK RETORIKA HABIB JA’FAR DALAM PROGRAM LOGIN CLOSETHEDOOR DI CHANNEL YOUTUBE DEDDY CORBUZIER - Muliani, Rahmi; Charlina; Sinaga, Mangatur (Universitas Muhammadiyah Surabaya, 2025)
This research aims to determine and describe Habib Ja'far's rhetorical techniques in the CloseTheDoor Login program on Deddy Corbuzier's Youtube Channel. In this research, the author used descriptive qualitative methods. The data in this research are Habib Ja'far's speech in the CloseTheDoor Login program. The data source in this research is the CloseTheDoor Login program which is broadcast on Deddy Corbuzier's YouTube Channel, consisting of 20 videos, 10 videos from season 1 and 10 videos from season 2. The data collection technique in this research uses listening and note-taking techniques. The data analysis technique in this research was carried out by reducing data, presenting data, and concluding data. Research results The results of this research are 50 data on pathos and logos techniques in Habib Ja'far. The most dominant techniques used are logos techniques with 29 data and pathos techniques with 21 data.